DMU Electric Drive Control System for Exporting Iraq - ZHOU Shaoyun; LI Xudong; LIU Songbai (机车电传动)
The main components and control object of DMU electric drive control system for exporting Iraq were introduced. The AC-DC main drive system, auxiliary AC drive system, battery charger system and their adaptive design were discussed in detail. Application indicated the stability and good performance of the electric drive system, which adapted the climatic environment of desert and gobi sand storm and high temperature.